Theory generation: from evidence to practice. - Congreso Internacional de Enfermería, Equipo organizador del Primer (Investigación y Educación en Enfermería, 2013)
The Faculty of Nursing at Universidad de Antioquia, designated as Chapter by the Roy Adaptation Association to boost knowledge and development of the theory in the practice, held the First International Congress on Nursing: Theory generation: from evidence to practice, this took place on March 8 and 9, 2013. This event was attended by Doctor Callista Roy, who is one of the biggest nursing theorists in the world. This academic meeting was an important opportunity to discuss possibilities for the development and academic consolidation of our discipline seeking to care for humans with ethical and social pertinence criteria, which are currently a priority.